Pengaruh Pengetahuan Kewirausahaan, Persepsi Risiko, Lingkungan Teknologi Terhadap Minat Berwirausaha - Finantyo Eddy Wibowo; Tina Nurdiani; Ahmad Nuh (FEB UNWIKU PURWOKERTO, 2021)
This study aims to determine the effect of Entrepreneurship Knowledge, Risk Perception and Technology Environment on Entrepreneurial Interests of STIS Al Wafa Bogor Students. The population used was 102 students with a sample of 50 respondents. This type of research is descriptive quantitative. Data collection technique using questionnaires, observations and interviews. Data analysis in this study used Multiple Linear Regression Analysis and classical assumption test using SPSS ver 26 program application. The sampling technique was purposive random sampling. Based on the results of the goodness of fit test, the independent variables tested individually that have a dominant influence on Entrepreneurial Intention are Entrepreneurial Knowledge and Technological Environment. Meanwhile, Risk Perception has no significant effect on the Entrepreneurial Intention